Oxygen uptake kinetics during moderate and heavy intensity exercise in humans: The influence of hypoxia and training status - Cleuziou, C.; Perrey, S.; Lecoq, A. M.; Candau, R.; Courteix, D.; Obert, P. (International Journal of Sports Medicine, 2005)
This study examined the influence of moderate hypoxia on the oxygen uptake (V·O2) kinetic response (primary time constant and slow component amplitude) during moderate and heavy cycle exercise in twenty-seven male subjects with various training status. Nine endurance trained (21.5 ± 2.6 yr), nine sprint trained (22.9 ± 5.7 yr), and nine untrained controls (24.0 ± 4.4 yr) completed incremental tests to exhaustion in normoxia (inspired gas concentration or FIO2 = 21 % O2) and hypoxia (FIO2 = 13 % O2) to establish the FIO2-specific ventilatory threshold (VT) and maximal VO2. Subsequently, the subjects performed repeated constant work rate cycling exercises during 7 min at moderate intensity (80 % of FIO2-specific VT) and heavy intensity (midway between the FIO2 specific VT and maximal VO2). Pulmonary gas exchange was measured breath-by-breath during all exercise sessions. For both moderate and heavy intensities, the time constant of the primary VO2 component was significantly (p < 0.05) slowed by ~ 25 to 30 % in hypoxia compared to normoxia to the same extent in the three groups. Hypoxia produced a more important decrease in the amplitude of the slow component in endurance athletes (- 36 %) than in sprinters (- 30 %) and controls (- 12 %). These results suggest that both primary and slow components of VO2 kinetics during the adjustment to moderate- and heavy-intensity exercise are sensitive to hypoxia while training status tended to modulate partly the slow component amplitude.